Effectiveness of vero cell inactivated vaccine against severe acute respiratory infections (SARI) in Sibu, Malaysia: A retrospective test-negative design. Issue 1 (31st December 2023) - Toh, Teck-Hock; Qi, Yang-Yang; Yong, Sook-Min; Lee, Jeffrey Soon-Yit; Liyana, Nur Fatin; See, Raymond Yon-Han; Teh, Jo-Hun; Toh, Aw-Zien; Naing, Lin; Dahian, Kamilah; Liew, Jun-Wei; Mose, Caisha Nivenia; et al.
ABSTRACT: The effectiveness of the vero cell inactivated vaccine (CoronaVac®) against severe acute respiratory infection (‎SARI)‎ caused by SARS-CoV-2 in the real world was assessed. A matched test-negative case-control design was employed using the web-based national information system, as well as the hospitalization dataset in Sibu Hospital. Vaccine effectiveness was measured by conditional logistic regression with adjustment for gender, underlying comorbidity, smoking status, and education level. Between 15 March and 30 September 2021, 838 eligible SARI patients were identified from the hospitalization records. Vaccine effectiveness was 42.4% (95% confidence interval [CI]: −28.3 to 74.1) for partial vaccination (after receiving the first dose to 14 days after receiving the second dose), and 76.5% (95% CI: 45.6 to 89.8) for complete vaccination (at 15 days or more after receiving the second dose). This analysis indicated that two doses of CoronaVac® vaccine provided efficacious protection against SARI caused by SARS-CoV-2 in the short term. However, the duration of protection, and performance against new variants need to be studied continuously.